Legal Implementation of Compensation Policies in Recovering State Losses from Corruption - Ricci Ricci; Mella Ismelina Farma Rahayu; Ade Adhari (Universitas Negeri Semarang, 2026)
Asset tracking and confiscation of assets from corruption crimes committed by three law enforcement agencies have not shown satisfactory results. This study uses a normative legal research method (doctrinal legal research) with a primary focus on corruption cases. This research method was adopted because the payment of Replacement Money in corruption cases has not been fully implemented optimally. Many corruption cases still impose additional penalties in the form of Replacement Money, and corruptors transfer assets to third parties before the state confiscates them. This study uses 3 (three approaches, namely the conceptual approach, the statutory approach, and the case approach. The results of this study indicate that the payment of Replacement Money in corruption cases aims to recover state losses by ratifying Law Number 7 of 2006 on the Ratification of the United Nations Convention on the Eradication of Corruption, 2003. This is done to implement a reverse-verification process for prospective officials before they take office. The practice of paying compensation in corruption cases, which are economic crimes, should prioritise fines or similar penalties. If the perpetrator of corruption fails to pay the fine or compensation, law enforcement (prosecutors), as the implementing agency, will form a team to track down the embezzled assets and seize them to compensate the state for losses.